2017
DOI: 10.4103/jips.jips_62_17
|View full text |Cite
|
Sign up to set email alerts
|

Demineralized dentin matrix scaffolds for alveolar bone engineering

Abstract: From the point of view of implant dentistry, this review discusses the development and clinical use of demineralized dentin matrix (DDM) scaffolds, produced from the patient's own extracted teeth, to repair alveolar bone defects. The structure and the organic and inorganic components of DDM are presented to emphasize the similarities with autogenous bone. Studies of DDM properties, such as osteoinductive and osteoconductive functions as well as efficacy and safety, which are mandatory for its use as a bone gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 51 publications
(67 reference statements)
0
54
0
6
Order By: Relevance
“…Autogenous tooth bone is consisted of demineralized dentin matrix (DDM) largely which is demineralized from dentin, a mainly structure of teeth [32]. The DDM which is the internal stuff may arouse less auto-immunity, therefore the less swelling and pain happened.…”
Section: Discussionmentioning
confidence: 99%
“…Autogenous tooth bone is consisted of demineralized dentin matrix (DDM) largely which is demineralized from dentin, a mainly structure of teeth [32]. The DDM which is the internal stuff may arouse less auto-immunity, therefore the less swelling and pain happened.…”
Section: Discussionmentioning
confidence: 99%
“…Although numerous bone morphogenetic protein (BMP) carriers have been tested, such as collagen, demineralized bovine bone, and hydroxyapatite, these carriers have several shortcomings, such as rapid resorption, lack of long-term maintenance of volume, and incompetent release of BMP. Processed demineralized dentin is already recognized as a rhBMP-2 carrier, since it facilitates induction of new bone formation and helps to release BMP slowly [44]. A recent animal study by Kim et al demonstrated that DDM dissolves rhBMP-2 more gradually and steadily than other tricalcium phosphates (TCP) and bovine bone, establishing that particulated DDM is the most effective BMP carrier [31].…”
Section: Discussionmentioning
confidence: 99%
“…Dentin and bone have similar compositions, consisting of 18% collagen, 70% hydroxyapatite, and 2% noncollagenous protein [24]. Besides the type I collagens in dentin, microporous dentinal tubules can seize BMP solution and widen the contact area with proteins which can facilitate the continuous binding and release of BMPs [19,44].…”
Section: Discussionmentioning
confidence: 99%
“…DDM is produced by acid extraction of dentin through a process that removes the inorganic mineral component and leaves a type I collagen framework. 24 Demineralization also exposes HD-GFs, including ED-BMPs, and improves the osteoinductivity of DDM. 25 The degree of demineralization achieved when using 24% ethylenediaminetetraacetic acid was not available.…”
Section: Preparation Of Demineralized Dentin Matrix As a Carrier Formentioning
confidence: 99%